PENYULUHAN DAN PEMBUATAN PUPUK ORGANIK UNTUKMENINGKATKAN PRODUKSI HASIL PANEN - A.F Djunaedi (UII, 2013)
At this time the view of development of organic agriculture as one of thealternative technologies for tackling environmental issues is needed. Major problems thatoccur due to soil contamination that causes supply of nutrients in the soil areincreasingly depleted. Moreover, many elements are missing are not returned to theground. If this goes on continuously, it will be increasingly poor soil nutrients. This canbe overcome by the use of fertilizers. However, chemical-based fertilizers when usedcontinuously will make a new problem for the soil. For that counseling manufacture oforganic fertilizer is given in order to become one of the solutions to improve yieldsresidents.